Effect of Ni/Sn ratio on martensitic transformation and magnetic properties in high‐Mn content Mn2Ni1.64−xSn0.36+x ferromagnetic shape memory alloys. Issue 3 (5th January 2015) - Xuan, H. C.; Zhang, Y. Q.; Li, H.; Han, P. D.; Wang, D. H.; Du, Y. W.
Abstract : The effect of variation in Ni/Sn ratio on martensitic transformation (MT) and magnetic properties was investigated in high‐Mn content Mn2 Ni1.64− x Sn0.36+ x alloys. With the increase of Sn content, the MT temperature shifts substantially towards lower temperature, while the Curie temperature of austenite remains almost unchanged. The reverse MT temperature decreases from 268 to around 80 K for Mn2 Ni1.64− x Sn0.36+ x alloys as x increases from 0.02 to 0.08. Under the low field of 1.2 T, the peak values of magnetic entropy changes are 9.8 J/kg K, 10.1 J/kg K, 10.3 J/kg K, and 6.1 J/kg K for x = 0.02, 0.04, 0.06, and 0.08, respectively. The abrupt changes in magnetization around MT temperatures and the field‐induced metamagnetism should account for the large magnetic entropy changes. Incorporating the advantages of inexpensive and non‐toxic raw materials, these high‐Mn content alloys exhibit very promising prospects for the applications in magnetic refrigeration.